THE ROLE OF ECONOMIC EDUCATION IN PROMOTING SUSTAINABLE ENTREPRENEURSHIP TO ACHIEVE THE SDGS - Adi Sucipto; Muhammad Yusuf Zamzami; Yohana Dian Puspitasari (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Economics education plays a crucial role in developing entrepreneurs who understand economic concepts, possess managerial skills, financial literacy, and sustainable business innovation. Within the context of the Sustainable Development Goals (SDGs), economics education contributes to job creation, inclusive economic growth, and socially and environmentally responsible businesses. Beyond simply transferring knowledge, this education shapes the character of creative, ethical, and sustainability-oriented entrepreneurs. Through a holistic approach, the values of business ethics, social responsibility, and environmentally friendly technology can be integrated into entrepreneurial practices. A literature review of research over the past five years shows that structured economics education can enhance individuals' capacity to build profitable businesses that positively impact society and the environment. Synergy between educational institutions, the government, and the private sector is needed to create an innovative and highly competitive entrepreneurial ecosystem.